How Can Online Resources for Cancer Patients Be Useful? - Cipolat Mis, Chiara; Costa, Camilla; Rizzolio, Flavio; Truccolo, Ivana (Informatica, 2022)
In the European Union, the necessity to help patients providing them with an equal, even if differentiated, kind of information about healthcare options is increasing. Patients have the same rights in any country to access prevention, diagnosis, and treatment of any type of disease. To achieve this end, the quality of information provided to the patients is crucial. Digital approaches aim at helping doctors and in general caregivers to reach all the patients to improve their empowerment, participation, and quality of life. In this paper, many questions are raised, and some solutions are provided including the INSIEME platform, where information about patient associations, companies, public and private services related to different types of pathologies in three languages are included.